Mechanical and thermal performance of a geopolymeric and hybrid material based on fly ash (2016)
This article presents an evaluation of the thermal behavior of a hybrid (FA/OPC) and geopolymer (FA100) material. The FA100 system is based on fly ash (FA), which has an elevated content of unburned material (14.8%). The FA/OPC system is comprised of a mixture of fly ash and ordinary Portland cement (OPC) at a proportion of 80/20. The thermal performance was evaluated by several tests, such as exposure to high temperatures (up to1000°C) and direct flame resistance. In addition, the effect of cyclic exposure was studied at 700°C for 10 cycles. FA/OPC hybrid material retains 92% of its initial strength and FA100 retains 113.3% of its initial strength at 700°C. Both materials can withstand 10 exposure cycles with a strength loss of less than 45%. In direct flame exposure, a temperature gradient of about 500°C was observed. These results indicate that these types of materials could possibly be used as fire-resistant materials in civil structures.